Prevalence of Fear of Falling and Its Association With Physical Function and Fall History Among Senior Citizens Living in Rural Areas of China - Su, Qingqing; Gao, Yuan; Zhang, Jie; Tang, Jingping; Song, Mi; Song, Jie; Mao, Yazhan; Pi, Hongying (Frontiers in Public Health, 2021)
Background: Fear of falling (FOF) is as significant as a fall, leading to limited physical activity and poor quality of life among senior citizens. This study aimed to investigate the prevalence of FOF and its association with physical function and fall history among the senior citizens (≥75 years old) living in rural areas of China. Methods: This was a cross-sectional study conducted in eastern China from June to October 2019. All elderly participants were recruited during their attendance for the free health examinations in villages and towns organized by the local healthcare authorities. Data on sociodemographics, fall history, FOF conditions, self-reported comorbidity and regular medications were collected by face-to-face interview, and the physical function status was evaluated through a field test. Univariate and multivariate analyses were performed to compare the differences in physical function and fall history of senior citizens with/without FOF. Results: A total of 753 senior citizens (mean age = 79.04) participated in this study. Of these, 63.5% were aged 75 to 80. FOF was reported in 22.8% of the participants, while 18.5% had a fall in the past year. Among the senior citizens with and without a fall history, the prevalences of FOF were 38.8% and 19.2%, respectively. On multivariate analyses, FOF was associated with the time Up and Go Test (TUG) duration (OR=1.080; 95%CI: 1.034-1.128), 4-Stage Balance Test score (OR=0.746; 95%CI: 0.597-0.0931), fall history (OR=2.633; 95%CI: 1.742-3.980), cerebral apoplexy (OR=2.478; 95%CI: 1.276-4.813) and comorbidities (≥ 2) (OR=1.637; 95%CI: 1.066-2.514), while the correlation between FOF and the 30-second chair stand test was only significant in univariate analysis (Z=-3.528, p<0.001). Conclusion: High prevalence of FOF is observed among the senior citizens living in rural areas of China. FOF is strongly correlated with physical function performance and fall history. Therefore, the implementation of targeted FOF prevention measures is key to improve the physical activity of the senior citizens, which would ultimately lead to fall prevention and improved quality of life.